2023
DOI: 10.1093/eurjpc/zwad035
|View full text |Cite
|
Sign up to set email alerts
|

Low QRS voltages and left ventricular hypertrophy: a risky association

Abstract: Background Low-QRS voltages (LQRSV) are an unexpected finding in left ventricular (LV) hypertrophy, i.e, hypertrophic cardiomyopathy (HCM) or athlete’s heart. Methods Prevalence and clinical correlates of LQRSV were investigated in 197 consecutive HCM patients, aged 58±13 years and comparatively in 771 Olympic athletes, aged 23± 4. Clinical characterization included family/personal history, symptoms, NYHA functional class, EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A recent study published by Pelliccia et al ( 94 ) demonstrated that low QRS voltages are present in 11% of patients with HCM and are associated with a larger extent of LGE on MRI ( Figure 5D,E ); furthermore, after a follow-up of 4.5 ± 2.6 years, the presence of LQRSV in HCM are associated with a higher incidence of functional deterioration, stroke, and ICD implant.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 78%
“…A recent study published by Pelliccia et al ( 94 ) demonstrated that low QRS voltages are present in 11% of patients with HCM and are associated with a larger extent of LGE on MRI ( Figure 5D,E ); furthermore, after a follow-up of 4.5 ± 2.6 years, the presence of LQRSV in HCM are associated with a higher incidence of functional deterioration, stroke, and ICD implant.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 78%
“…Recent studies have proposed criteria for LQRSV when screening athletes for cardiovascular disease. 30 These criteria have not yet been evaluated in a large population of healthy young athletes. The target population was 10,728 (42.5% female, 57.5% male, mean age 18.1 ± 4.3 years) athletes who participated in mass ECG screenings between 2014 and 2021 at multiple sites across the United States including grade schools (11%), high schools (32%), colleges (50%), and professional athletic teams (6%) with digitally recorded ECGs and a standardized protocol.…”
Section: The Stanford St Segment Studiesmentioning
confidence: 99%
“…In patients with HF with reduced ejection fraction, the presence of LBBB was associated with increased mortality (Baldasseroni et al., 2002 ; Witt et al., 2016 ). In contrast, the low QRS amplitude in subjects with LVH is reported as a cardiovascular risk factor (Bacharova et al., 2015 ; Pelliccia et al., 2023 ).…”
Section: Ecg‐lvh As An Independent CV Ris...mentioning
confidence: 99%
“…However, the ECG imparts unique information on the electric field associated with LVH. Increased QRS amplitude (Adam Leigh et al, 2016;Zhang et al, 2020), in the presence of LVH, are significant independent cardiovascular risk factors (Bacharova et al, 2015;Pelliccia et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation